Transceiver Design for Full-Duplex UAV Based Zero-Padded OFDM System With Physical Layer Security - Joarder Jafor Sadique; Shaikh Enayet Ullah; Md. Rabiul Islam; Raad Raad; Abbas Z. Kouzani; M. A. Parvez Mahmud (IEEE Access)
In this paper, multi-antenna transceiver for zero-padded orthogonal frequency division multiplexing (OFDM) system is designed at mmWave by integrating full-duplex unmanned aerial vehicle (UAV) into the terrestrial cellular networks. Assuming that there exist no direct communication links between the ground base station (GBS) and the mobile users due to unexpected blockages from high storied buildings in urban area, the UAV applies decode-and-forward cooperative strategy on the received OFDM signals transmitted from GBS and re-transmits to the ground mobile users and passive eavesdropper. In this proposed system, intertwining logistic map (ILM)-cosine transform aided encryption algorithm combined with artificial noise enhancing physical layer security (PLS) is introduced. Also walsh-hadamard transform technique integrated with QR-decomposition based zero forcing (ZF) block diagonalization (QR-ZF-BD) precoding for multi-user interference reduction and non-iterative clipping and filtering technique for peak to average power ratio (PAPR) reduction are utilized. In addition, Low density parity check (LDPC) and repeat and accumulate (RA) channel coding with cholesky decomposition based ZF and minimum mean square error signal detection schemes for improved bit error rate (BER) are also introduced. Numerical results demonstrate the effectiveness of the proposed system in terms of PLS for color image transmission at high order digital modulation (16-PSK and 16-QAM). At the complementary cumulative distribution function of probability level 1-6%, the estimated PAPR is found to have value of 6 dB.The three users achieve BER $= 1× {10}^{-4}$ at signal-to-noise ratio of 1.5 dB, 4 dB and 6 dB under RA channel coding and 16-QAM digital modulation.